Competitive Strategies when Consumers are Relative Thinkers: Implications for Pricing, Promotions, and Product Choice - Roman Inderst; Martin Obradovits (ZBW – Leibniz Information Centre for Economics, 2019)
How should firms optimally choose prices and promotional strategies and how should they position their products when consumers are "relative thinkers"? We provide answers in a model that extends the seminal contributions of Varian (1980) and Narasimhan (1988) and derive both managerial implications and implications for empirical researchers with regards to promotional frequency and depth as well as observed product heterogeneity in the market.
Keywords: 330